Analisis Identifikasi Produk Primer Unggulan Ekspor Indonesia dengan Menggunakan Pendekatan Indeks Komposit - Ardiyanti, Septika Tri; Pratiwi, Retno Ariyanti; Gunadi, Dwi; Amalia, Syarifah (Cendekia Niaga, 2025)
This analysis aims to identify superior export products, especially primary products which are the main contributors to national exports. In identifying superior primary export products, this analysis uses a Composite Index based on several indicators, including: i) import value and world import trends during the 2018-2022 period; ii) the share and growth of the share of Indonesian products in the world market; iii) export value and trend of Indonesian exports to the world during the 2018-2022 period; iv) share and growth in the share of product exports to total national exports; and v) product competitiveness as measured using the RSCA index. This analysis also projects the export value of selected primary export-leading products in 2024 using the ARIMA model and GARCH model. Based on the results of the analysis, potential primary export products that can be considered as a focus for developing and increasing exports in 2024 include processed cigarettes and tobacco, processed wood, processed shrimp, processed cocoa, coffee, CCO and its derivatives, vegetable ingredients, swallow nests, spices and seaweed. It is hoped that these superior primary products can become a focus for export development, making it easier to achieve national export growth targets and can be used as initial reference material for formulating policies to increase exports of primary products in 2024.